Trypanosoma cruzi-specific immune responses in subjects from endemic areas of Chagas disease of Argentina - Olivera, Gabriela Carina (2010)
Fil: Olivera, Gabriela Carina. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.